Overexpression of gamma-aminobutyric acid transporter subtype I leads to cognitive deterioration in transgenic mice - Ma Ying-Hua; Fei Jian; Hu Jia-Hua; Zhou Xiao-Gang; Xia Guo-Hong; Guo Li-He (Acta Pharmacologica Sinica; Vol 22, No 4 (Apri 2001): Acta Pharmacologica Sinica, 2016)
Aim: To explore the physiological role of gamma-aminobutyric acid transporter subtype I (GAT1) in cognition. Methods: Transgenic mice were produced by pronuclei microinjection method. Integration of transgene was identified by Southern-blot and PCR analysis in various generations. Level of GAT1 mRNA in a variety of tissues was evaluated by semi-quantitative RT-PCR analysis. GAT1 protein was detected by immunofluorescence and histochemistry analysis. Associative learning capacity was analyzed by conditioned avoidance task. Memory retention was assessed by novel object recognition test. Morphology of synaptosomes was examined by electron microscope. Results: Four independent founder mice bearing various copies of transgene were generated. GAT1 was evidently overexpressed at both mRNA and protein level in a variety of tissues from transgenic mice. In comparison with wild-type mice, transgenic mice exhibited significantly declined associative learning capacity (P < 0.01) and decreased memory retention (P < 0.01 in 1-h-retention, and P < 0.05 in 1-d-retention). In addition, the amount of asymmetric synapses in the brain of transgenic mice was reduced approximately by 24 %, relative to wild-type mice. Conclusion: Overexpression of GAT1 in mice results in cognitive deterioration, indicating that the alteration in the expression of gamma-aminobutyric acid transporters is involved in the pathophysiological mechanism underlying some cognitive deficiencies.